Persistent Primary Hyperparathyroidism Secondary to an Ectopic Mediastinal Adenoma in a Young Adult: A Case Report - Karl Homer; Alba, Rebecca (Journal of the ASEAN Federation of Endocrine Societies, 2023)
Primary hyperparathyroidism commonly affects elderly women. When present in the young population, it is usually asymptomatic, most frequently due to a parathyroid adenoma and the definitive management is surgical excision. Uncommonly, 5-10% of patients fail to achieve long-term cure after initial parathyroidectomy and 6-16% of them is due to an ectopic parathyroid adenoma that will require focused diagnostic and surgical approaches. We report a 21-year-old male who had bilateral thigh pain. Work-up revealed bilateral femoral fractures, brown tumors on the arms and multiple lytic lesions on the skull. Serum studies showed hypercalcemia (1.83 mmol/L), elevated parathyroid hormone [(PTH) 2025.10 pg/mL], elevated alkaline phosphatase (830 U/L), normal phosphorus (0.92 mmol/L) and low vitamin D levels (18.50 ng/mL). Bone densitometry showed osteoporotic findings. Sestamibi scan showed uptake on the left superior mediastinal region consistent with an ectopic parathyroid adenoma. Vitamin D supplementation was started pre-operatively. Patient underwent parathyroidectomy with neck exploration; however, the pathologic adenoma was not visualized and PTH levels remained elevated post-operatively. Chest computed tomography with intravenous contrast was performed revealing a mediastinal location of the adenoma. A repeat parathyroidectomy was done, with successful identification of the adenoma resulting in a significant drop in PTH and calcium levels. Patient experienced hungry bone syndrome post-operatively and was managed with calcium and magnesium supplementation. A high index of suspicion for an ectopic adenoma is warranted for patients presenting with hypercalcemia and secondary osteoporosis if there is persistent PTH elevation after initial surgical intervention. Adequate follow-up and monitoring is also needed starting immediately in the post-operative period to manage possible complications such as hungry bone syndrome.